PENGEMBANGAN KOMPETENSI KEPEMIMPINAN SEJAK DINIBAGI SISWA PADA SMK BUANA MULIAPARUNG PANJANG BOGOR - Bambang Sutarto; Gunarda Gunarda; Wahadi Siamto (Jurnal Pengabdian Tangerang Selatan [JURANTAS], 2026)
Early leadership competence development is a fundamental aspect in shaping students' character and readiness to face challenges in the workplace and community life. This Community Service Program (PKM) aims to enhance leadership competencies of students at SMK Buana Mulia Parung Panjang Bogor through a series of structured training activities and workshops. The implementation method uses a participatory approach with a combination of interactive lectures, group discussions, leadership simulations, and direct practice during the period of March 7-9, 2026. The activity was attended by 45 students from grades X and XI who were selected through a selection process based on leadership potential and learning motivation. The results showed a significant increase in understanding of leadership concepts, with an average pre-test score of 65.2 increasing to 82.8 on the post-test, indicating a 27% improvement in material mastery. Participant evaluation showed that 87% of students felt more confident in taking leadership roles and 92% stated that the activity was very beneficial for their personal development. The conclusion from this activity indicates that structured leadership training programs are effective in increasing the competence and motivation of vocational high school students in developing leadership spirit from an early age